2021
DOI: 10.1002/wer.1496
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the use of microalgal–bacterial consortia for wastewater treatment: Community structures, interactions, economic resource reclamation, and study techniques

Abstract: The rise in living standards has generated a demand for higher aquatic environmental quality. The microalgal community and the surrounding organic molecules, environmental factors, and microorganisms, such as bacteria, are together defined as the phycosphere. The bacteria in the phycosphere can form consortia with microalgae through various forms of interaction. The study of the species in these consortia and their relative proportions is of great significance in determining the species and strains of stable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 101 publications
0
28
0
Order By: Relevance
“…In this study, a physicochemical characterization was carried out following NOM-001-SEMARNAT-199617, considering all the parameters to determine the variations once the phytoremediation process has been implemented. The microbiological study of the treated samples showed that Pseudomonas sp., in 75% of the isolates from the wastewater from the Alseseca-Sur WWTP, using the effluent water as a culture medium for the growth of C. vulgaris without requiring a simulated medium, thus taking advantage of the characteristics present in the initial sample, in contrast to what has been reported in various studies where phytoremediation processes are carried out with C. vulgaris inoculating certain species of Pseudomonas, Bacillus and bacterial consortia to favor the efficiency of the system in the removal of pollutants present in wastewater (Mu et al, 2020); the data on the increase in the concentration of C. vulgaris with wastewater as a culture medium are similar to those reported in Shen et al, (2017) where they report an increase in the cell density of C. vulgaris in symbiosis with Pseudomonas putida using municipal wastewater as a culture medium, removing ammonium, phosphates and organic compounds from the wastewater. However, in the present work the decrease was in all the physicochemical parameters established in NOM-001-SEMARNAT-199618, except for hardness.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, a physicochemical characterization was carried out following NOM-001-SEMARNAT-199617, considering all the parameters to determine the variations once the phytoremediation process has been implemented. The microbiological study of the treated samples showed that Pseudomonas sp., in 75% of the isolates from the wastewater from the Alseseca-Sur WWTP, using the effluent water as a culture medium for the growth of C. vulgaris without requiring a simulated medium, thus taking advantage of the characteristics present in the initial sample, in contrast to what has been reported in various studies where phytoremediation processes are carried out with C. vulgaris inoculating certain species of Pseudomonas, Bacillus and bacterial consortia to favor the efficiency of the system in the removal of pollutants present in wastewater (Mu et al, 2020); the data on the increase in the concentration of C. vulgaris with wastewater as a culture medium are similar to those reported in Shen et al, (2017) where they report an increase in the cell density of C. vulgaris in symbiosis with Pseudomonas putida using municipal wastewater as a culture medium, removing ammonium, phosphates and organic compounds from the wastewater. However, in the present work the decrease was in all the physicochemical parameters established in NOM-001-SEMARNAT-199618, except for hardness.…”
Section: Resultsmentioning
confidence: 99%
“…[157,158] The commercial application of microalgae for biomass production using wastewater has been started since 1950s. [159] Wastewater as a growth medium for microalgae that cannot only utilize inorganic and organic nutrients metabolically but also in the cooperation with microbes to degrade/metabolize other pollutants with significant public health and environmental threat, like polyaromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), pesticides, insecticides, phenolics, petroleum hydrocarbons (PHCs), heavy metals, and antibiotics, [160][161][162] is a readily accessible and inexpensive approach [163,164] for WWT coupled with microalgae growth to offer cost-effective biomass feedstock and biofuel generation. [165][166][167] Initially, research into the use of wastewater-grown microalgae for energy production started with the use of microalgae as a feedstock for methane production.…”
Section: Potential Development Of Genetic Engineering Of Microalgae F...mentioning
confidence: 99%
“…Several research works at laboratory-scale have demonstrated the extraordinary capabilities of microalgae to treat wastewater of various origins, either directly or after pre-treatment processes [ 40 ]. More recently, microalgal-bacterial sludge based processes have attracted increasing attention due to the mutualistic and symbiotic relationship that microalgae and bacteria can establish [ 41 ]. The oxygen produced via photosynthesis by the microalgae cells can be used by the bacteria to oxidize organic matter, thus allowing for the collaboration between the microalgae and aerobic bacteria in the same system.…”
Section: Biomassmentioning
confidence: 99%